Graduate nurses' capability upon entering the workforce: An integrative review. (February 2023) - Saghafi, Farida; Bromley, Patricia; Guzys, Diana; Harkness, Leigh; Phillips, Michelle; Mather, Carey; Saunders, Annette; Say, Richard; Teare, Catherine; Tori, Kathleen
Abstract: Objectives: To clarify capability for work readiness in newly graduated registered nurses as viewed from the perspective of clinicians in practice, educators in tertiary institutions, and graduates. Design: Integrative review. Data sources: Databases searched for peer-reviewed studies included PubMed, MEDLINE, ERIC, Campbell collaboration, Google Scholar, and Cochrane databases. Review methods: Pragmatism informed this integrative review. The five-stage method described by Whittemore and Knafl was used to enable rigorous examination of the expected capability of graduate nurses. A comprehensive database search was conducted using PRISMA guidelines. Eighteen articles were appraised and analysed for this review. The capability concept was used as a framework for analysis. Results: Eighteen articles met the inclusion criteria. Findings revealed that although there is no definition for graduate nurses' work readiness, there is a common theme. Graduate nurses are expected to have broad theoretical knowledge (knowing) along with practical knowledge (doing). They are also expected to demonstrate integrity, honesty, respect, compassion, and a moral compass. A list of personal attributes and organisational acumen was also reflective of graduate readiness upon entering the workforce and identified as necessary capabilities for graduates. Conclusions: A picture of the perfect employee is illustrated in the definition of work readiness by the participants of the original studies. Yet there is a lack of stakeholder consensus on the capabilities expected from a graduate nurse. Highlights: There is a lack of accepted attributes or consensus on expected graduate nurse capability upon entering the workforce. For over 25 years, the main themes echoing the holistic model of nursing professional competence have not changed. Overt direction regarding the development of graduate capability needs to be clearly articulated within undergraduate nursing curricula. More research is needed on the extent of the expected capability for graduate nurses upon entering the workforce.